1999
DOI: 10.1097/00000542-199912000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-induced Depression of Cultured Rat Ventricular Myocytes Is Related to the M2-acetylcholine Receptor–NO–cGMP Signaling Pathway 

Abstract: These results suggest that the negative chronotropy induced by propofol is mediated in part by M2-acetylcholine receptor activation, which involves the enhancement of NO production in cultured rat ventricular myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…The decrease in blood pressure without any change in the heart rate at T2 and T5 indicate that propofol attenuated the baroreflex activity [28], despite the increase of the cardiac sympathetic activity. In an animal study, propofol was shown to exert a negative chronotropic effect in a dose-dependent manner [29]. The discrepancy between the change in heart rate and cardiac autonomic activity in our study showed that propofol had direct effects on the heart.…”
Section: Discussioncontrasting
confidence: 57%
“…The decrease in blood pressure without any change in the heart rate at T2 and T5 indicate that propofol attenuated the baroreflex activity [28], despite the increase of the cardiac sympathetic activity. In an animal study, propofol was shown to exert a negative chronotropic effect in a dose-dependent manner [29]. The discrepancy between the change in heart rate and cardiac autonomic activity in our study showed that propofol had direct effects on the heart.…”
Section: Discussioncontrasting
confidence: 57%
“…Propofol administration should also be considered another potential source of bradycardia. Propofol can cause bradycardia through β-2 adrenergic receptors block [23] or through M-2 acetylcholine receptor activation [24]. However, in the clinical setting, the occurrence of bradycardia with propofol (in the absence of concomitant opioid administration) has been reported only when associated with preexisting myocardial depression [25] or as part of the propofol infusion syndrome (PRIS) [26].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured porcine aortic endothelial cells and rat ventricular myocytes, PPF has been shown to enhance NO production and cause the vasodilatation or negative chronotropy (Petros et al 1993;Yamamoto et al 1999). A study on canine pulmonary arterial rings revealed that PPF selectively attenuated acetylcholine-induced relaxation by inhibiting NO synthesis (Beutler and Poltorak 2001).…”
Section: Introductionmentioning
confidence: 99%